2014
DOI: 10.2486/indhealth.2013-0138
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characteristics and Robustness of an Inclined Quad-vortex Range Hood

Abstract: A novel design of range hood, which was termed the inclined quad-vortex (IQV) range hood, was examined for its flow and containment leakage characteristics under the influence of a plate sweeping across the hood face. A flow visualization technique was used to unveil the flow behavior. Three characteristic flow modes were observed: convex, straight, and concave modes. A tracer gas detection method using sulfur hexafluoride (SF6) was employed to measure the containment leakage levels. The results were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Their results showed that adding side plates improved the capture efficiency by 20%. Meanwhile, Huang et al installed two side plates at the lateral ends of a hood to increase containment removal efficiency and reduce energy consumption. The relative leakage of contaminant from the hood into the occupied zone became virtually non‐existent.…”
Section: Improvement Measures For Kitchen Ventilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that adding side plates improved the capture efficiency by 20%. Meanwhile, Huang et al installed two side plates at the lateral ends of a hood to increase containment removal efficiency and reduce energy consumption. The relative leakage of contaminant from the hood into the occupied zone became virtually non‐existent.…”
Section: Improvement Measures For Kitchen Ventilationmentioning
confidence: 99%
“…Their results showed that adding side plates improved the capture efficiency by 20%. Meanwhile, Huang et al 60,61…”
Section: Improving Range Hood Designmentioning
confidence: 99%
“…Local exhaust ventilation (range hood) is an effective method to capture contaminants in residential buildings. To improve the efficiency for capturing contaminants and provide healthier indoor air quality, some innovative technologies had been studied: Aaberg hood [6][7][8][9][10][11][12], separation plate technology [13][14][15], air curtain technology [16][17][18][19][20][21][22][23], tornado-like suction airflow technology [24,25], and make-up air technology [26][27][28][29]. Some optimizations of the range hood have been proposed: Shaping the outlet [30], changing the structure of the fan [31,32], and adjusting some influential factors (airflow rate, dimension, and burner * Corresponding author: fl@byg.dtu.dk position of the range hood) [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%